A kind of lithium ion battery water-based fire extinguishing agent and preparation process

CN119185881BActive Publication Date: 2025-02-28MOLIFANG TECH (BEIJING) CO LTD

Patent Information

Application Number
CN202411319825.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-28
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Existing water-based fire extinguishing agents have the risk of electric shock and rekindling when extinguishing lithium-ion battery fires.

Method used

A lithium-ion battery water-based fire extinguishing agent including water, starch grafted ammonium phosphate-monmortem complex, polyol, saponin, potassium perfluorobutylsulfonate, diethylene glycol monobutyl ether, nanosilica and sodium carboxymethylcellulose are used to form a protective film of nanosilica by flame retardant action of starch grafted ammonium phosphate-monmortem complex and a protective film of nanosilica to prevent oxygen and heat transfer and prevent rekindle.

Benefits of technology

It effectively reduces the risk of electric shock and rekindling of lithium-ion battery fires when extinguishing fires, and ensures the complete fire extinguishing and cooling effect of the fire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005053523970000011
    Figure HDA0005053523970000011
Patent Text Reader

Abstract

The present application relates to the technical field of lithium-ion battery fire extinguishing agents, and in particular to a lithium-ion battery water-based fire extinguishing agent and a preparation process. According to mass parts, the lithium-ion battery water-based fire extinguishing agent includes 70 to 80 parts of water, 25 to 35 parts of starch-grafted ammonium phosphate-montmorillonite complex, 15 to 25 parts of polyols, 5 to 10 parts of saponin, 3 to 5 parts of potassium perfluorobutyl sulfonate, 10 to 15 parts of diethylene glycol monobutyl ether, 3 to 5 parts of N, N-diethyl-1,3-propylenediamine, 4 to 6 parts of nano-silicon dioxide, and sodium carboxymethyl cellulose, wherein the sodium carboxymethyl cellulose is 5 to 7% of the mass of the starch-grafted ammonium phosphate-montmorillonite complex; the starch-grafted ammonium phosphate-montmorillonite complex includes starch, montmorillonite, ammonium phosphate, ammonium persulfate, ethyl acetate and sodium dodecyl sulfate. The embodiment of the present application provides a lithium-ion battery water-based fire extinguishing agent and a preparation process to solve the problem of electric shock risk and re-ignition risk when the water-based fire extinguishing agent extinguishes the lithium-ion battery in the related art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion battery fire extinguishing agents, and in particular to a lithium-ion battery water-based fire extinguishing agent and a preparation process thereof. Background Art

[0002] At present, lithium-ion battery fires occur frequently. Since lithium-ion batteries rely on internal chemical reactions to charge and discharge, if a short circuit or overheating occurs, the battery temperature will rise rapidly. When the temperature reaches a certain level, the chemical reaction inside the battery will go out of control, releasing a large amount of flammable gas and heat, thus causing a fire.

[0003] In the prior art, dry powder fire extinguishers, carbon dioxide fire extinguishers and water-based fire extinguishers are usually used to extinguish lithium-ion battery fires. However, dry powder fire extinguishers will leave a large amount of residue after extinguishing the fire, making it difficult to effectively cool the battery, which may cause the battery to reignite after the fire is extinguished. The cooling effect of carbon dioxide fire extinguishers is limited and is not suitable for lithium battery fire extinguishing.

[0004] Water-based fire extinguishing agents are low-cost and do not leave a lot of dust residue like dry powder fire extinguishers after extinguishing a fire, which causes less pollution to the environment. At the same time, its composition is relatively simple and is not likely to cause long-term adverse effects on soil, water sources, etc. It is more environmentally friendly, so it is necessary to develop a water-based fire extinguishing agent for lithium-ion batteries.

[0005] However, on the one hand, water itself is conductive. When using water-based fire extinguishing agents to put out a fire, if the battery is still charged and leaks electricity, it may cause a risk of electric shock and a short circuit, further damaging the battery or other electronic equipment, or even causing a new fire or safety accident. On the other hand, the main cause of lithium-ion battery fires is thermal runaway, and the internal chemical reactions are complex and violent. Although water-based fire extinguishing agents can lower the temperature, they may not be able to completely terminate the chemical reactions inside the battery. After the fire is extinguished, the battery may experience thermal runaway again due to the high temperature and active substances still present inside, leading to reignition. Summary of the invention

[0006] The present application provides a lithium-ion battery water-based fire extinguishing agent and a preparation process to solve the problem of electric shock risk and re-ignition risk when the water-based fire extinguishing agent is used to extinguish lithium-ion batteries in the related art.

[0007] In a first aspect, a lithium-ion battery water-based fire extinguishing agent is provided, which comprises, in parts by mass:

[0008] 70-80 parts of water, 25-35 parts of starch grafted ammonium phosphate-montmorillonite composite, 15-25 parts of polyol, 5-10 parts of saponin, 3-5 parts of potassium perfluorobutyl sulfonate, 10-15 parts of diethylene glycol monobutyl ether, 3-5 parts of N,N-diethyl-1,3-propylenediamine, 4-6 parts of nano silicon dioxide, and sodium carboxymethyl cellulose, wherein the sodium carboxymethyl cellulose accounts for 5-7% of the mass of the starch grafted ammonium phosphate-montmorillonite composite;

[0009] The starch grafted ammonium phosphate-montmorillonite composite comprises starch, montmorillonite, ammonium phosphate, ammonium persulfate, ethyl acetate and sodium dodecyl sulfate, and the mass ratio of the starch, montmorillonite, ammonium phosphate, ammonium persulfate, ethyl acetate and sodium dodecyl sulfate is 100:50:15:0.4:5.4:2.4.

[0010] Preferably, the polyol includes one of xylitol and sorbitol.

[0011] Preferably, it further comprises guar gum, and the guar gum accounts for 2-4% of the total mass of the fire extinguishing agent.

[0012] In a second aspect, a preparation process of a lithium-ion battery water-based fire extinguishing agent is provided, which is used to prepare any of the lithium-ion battery water-based fire extinguishing agents described above, and comprises the following steps:

[0013] S1, mixing 25-35 parts of starch grafted ammonium phosphate-montmorillonite composite with 70-80 parts of water, and adding sodium carboxymethyl cellulose to obtain a composite suspension;

[0014] S2, adding 15-25 parts of polyol, 5-10 parts of saponin, 3-5 parts of potassium perfluorobutyl sulfonate, 10-15 parts of diethylene glycol monobutyl ether, 4-6 parts of nano-silicon dioxide and sodium carboxymethyl cellulose to the composite suspension in sequence, and stirring at 25° C. for 1 hour, wherein the total amount of sodium carboxymethyl cellulose added to S1 and S2 is 5-7% of the starch grafted ammonium phosphate-montmorillonite composite;

[0015] S3. Add 3 to 5 parts of N,N-diethyl-1,3-propylenediamine to the solution obtained in S2, and ultrasonically treat for 30 minutes to obtain a lithium-ion battery water-based fire extinguishing agent.

[0016] Preferably, the preparation method of the starch grafted ammonium phosphate-montmorillonite composite comprises the following steps:

[0017] Starch pretreatment: mix starch and deionized water in a mass ratio of 1:3 to 1:5, heat to 60 to 80°C for gelatinization, and stir evenly to obtain a starch solution;

[0018] Surface treatment of montmorillonite: dispersing montmorillonite of 20 to 50 nm in a dispersant solution at a mass volume ratio of 1:5 to 1:8, stirring at 40 to 60° C. for 1 to 2 hours to perform surface treatment and obtain a montmorillonite dispersion;

[0019] Starch grafted ammonium phosphate: the montmorillonite dispersion is added dropwise to the starch solution under continuous stirring, so that the mass ratio of montmorillonite to starch is 1:2-1:3, after stirring evenly, ammonium phosphate and ammonium persulfate are added, and under continuous stirring, the mixture is reacted at 50-70° C. for 2-4 hours to obtain a primary product, wherein the mass ratio of ammonium phosphate to starch is 1:1.4, and the ammonium persulfate is 2% of the mass of the starch;

[0020] Post-treatment: The primary product is filtered, washed and dried to obtain a starch-grafted ammonium phosphate-montmorillonite composite.

[0021] Preferably, the dispersant solution comprises 3 wt % of sodium dodecyl sulfate solution and 2 wt % of ethyl acetate solution, and the volume ratio of the sodium dodecyl sulfate solution to the ethyl acetate solution is 3:2.

[0022] Preferably, in S3, after adding N,N-diethyl-1,3-propylenediamine and ultrasonic treatment, the step further comprises:

[0023] Add 2-4% guar gum by weight of the total mass of the solution to the solution after ultrasonic treatment, stir for 30 minutes, and obtain a lithium ion battery water-based fire extinguishing agent.

[0024] The beneficial effects of the technical solution provided by this application include:

[0025] The present application provides a water-based fire extinguishing agent for lithium-ion batteries and a preparation process thereof. A large amount of water plays a role in cooling and takes away the heat generated by the combustion of the lithium-ion battery in the form of evaporation. The starch-grafted ammonium phosphate-montmorillonite composite plays a flame retardant role at high temperatures. The ammonium phosphate decomposes to produce non-combustible gas and a heat-insulating layer to dilute the oxygen concentration around the battery. The montmorillonite forms a barrier layer to prevent oxygen and heat transfer. Saponin and potassium perfluorobutyl sulfonate allow the fire extinguishing agent to form a uniform water film on the surface of the battery to block oxygen and not soak the battery. Xylitol and diethylene glycol monobutyl ether ensure that the fire extinguishing agent has stable performance at different temperatures. Nano-silicon dioxide enhances the stability and heat resistance of the fire extinguishing agent and reduces viscosity and conductivity. After the temperature is initially reduced, silicon dioxide can form a protective film on the surface of the battery to prevent the combustibles inside the battery from contacting with oxygen and avoiding re-ignition. Therefore, the problem of electric shock risk and re-ignition risk when the water-based fire extinguishing agent is used to extinguish lithium-ion batteries in the related art can be solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 A flow chart of the preparation process of the lithium-ion battery water-based fire extinguishing agent provided in this application;

[0028] Figure 2 This is a flow chart of the method for preparing the starch grafted ammonium phosphate-montmorillonite composite provided in an embodiment of the present application. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0030] The present application provides a preparation process of a water-based fire extinguishing agent for lithium-ion batteries, which can solve the problem of electric shock risk and re-ignition risk when water-based fire extinguishing agents are used to extinguish lithium-ion batteries in the related art. The process includes the following steps:

[0031] S1. Mix 25 to 35 parts of starch grafted ammonium phosphate-montmorillonite composite with 70 to 80 parts of water, and add sodium carboxymethyl cellulose to obtain a composite suspension; specifically, sodium carboxymethyl cellulose is used as a stabilizer and is adsorbed on the surface of the starch grafted ammonium phosphate-montmorillonite composite to prevent particle aggregation and sedimentation through electrostatic repulsion and steric hindrance, thereby maintaining the uniformity and stability of the fire extinguishing agent.

[0032] S2, adding 15-25 parts of polyol, 5-10 parts of saponin, 3-5 parts of potassium perfluorobutyl sulfonate, 10-15 parts of diethylene glycol monobutyl ether, 4-6 parts of nano silicon dioxide and sodium carboxymethyl cellulose to the composite suspension in sequence, and stirring at room temperature for 1 hour, the total amount of sodium carboxymethyl cellulose added in S1 and S2 is 5-7% of the starch grafted ammonium phosphate-montmorillonite composite;

[0033] S3. Add 3 to 5 parts of N,N-diethyl-1,3-propylenediamine to the solution obtained in S2, and ultrasonically treat for 30 minutes to obtain a lithium-ion battery water-based fire extinguishing agent.

[0034] In some embodiments, the preparation method of the starch grafted ammonium phosphate-montmorillonite composite comprises the following steps:

[0035] Starch pretreatment: mix starch and deionized water in a mass ratio of 1:3 to 1:5, heat to 60 to 80°C for gelatinization, and stir evenly to obtain a starch solution;

[0036] Surface treatment of montmorillonite: dispersing montmorillonite of 20 to 50 nm in a dispersant solution at a mass volume ratio of 1:5 to 1:8, stirring at 40 to 60° C. for 1 to 2 hours to perform surface treatment and obtain a montmorillonite dispersion;

[0037] Starch grafted ammonium phosphate: the montmorillonite dispersion is added dropwise to the starch solution under continuous stirring to make the mass ratio of montmorillonite to starch be 1:2-1:3. After stirring evenly, ammonium phosphate and ammonium persulfate are added, and the mixture is reacted at 50-70°C for 2-4 hours under continuous stirring to obtain a primary product. Specifically, the mass ratio of ammonium phosphate to starch is 1:1.4, and the ammonium persulfate is 2% of the mass of the starch.

[0038] Post-treatment: The primary product is filtered, washed and dried to obtain a starch-grafted ammonium phosphate-montmorillonite composite.

[0039] Specifically, ammonium phosphate decomposes at high temperature to produce non-combustible gas and a heat-insulating layer, which plays a flame retardant role. The gelatinized starch has better reactivity and, as the main body of the grafting reaction, undergoes a grafting reaction with ammonium phosphate to improve the flame retardant properties. After the ammonium phosphate is grafted with the starch, the stability and dispersibility are improved. It is further compounded with montmorillonite. The layered structure of montmorillonite can enhance its barrier properties and prevent the transfer of oxygen and heat. After surface treatment, it is more tightly bonded to the starch-grafted ammonium phosphate, further improving the stability and dispersibility of the composite.

[0040] Preferably, the dispersant solution comprises 3 wt % of sodium dodecyl sulfate solution and 2 wt % of ethyl acetate solution, and the volume ratio of the sodium dodecyl sulfate solution to the ethyl acetate solution is 3:2.

[0041] In some embodiments, in S3, after adding N,N-diethyl-1,3-propylenediamine and ultrasonic treatment, the following steps are further included:

[0042] Add 2-4% guar gum by weight of the total mass of the solution to the solution after ultrasonic treatment, stir for 30 minutes, and obtain a lithium ion battery water-based fire extinguishing agent.

[0043] Specifically, adding guar gum can appropriately increase the viscosity of the water-based fire extinguishing agent, so that the fire extinguishing agent forms a more stable water film on the battery surface, and enhances the effect of blocking oxygen. At the same time, guar gum can also improve the adhesion of the fire extinguishing agent, so that it can better adhere to the battery surface and prolong the fire extinguishing time; the amount of guar gum added is set to 2-4% of the total mass of the solution after ultrasonic treatment, and the viscosity of the fire extinguishing agent will not increase too significantly, while the fire extinguishing effect can be improved.

[0044] Example 1

[0045] The preparation process of the lithium ion battery water-based fire extinguishing agent provided in this embodiment comprises the following steps:

[0046] S1, mixing 25 parts of starch grafted ammonium phosphate-montmorillonite composite with 70 parts of water, and adding 1 part of sodium carboxymethyl cellulose to obtain a composite suspension;

[0047] S2, adding 15 parts of xylitol, 5 parts of saponin, 3 parts of potassium perfluorobutyl sulfonate, 10 parts of diethylene glycol monobutyl ether, 4 parts of nano-silicon dioxide, and 0.25 parts of sodium carboxymethyl cellulose to the composite suspension in sequence, and stirring at room temperature for 1 hour;

[0048] The total amount of sodium carboxymethyl cellulose added to S1 and S2 is 5% of the starch-grafted ammonium phosphate-montmorillonite composite.

[0049] S3. Add 3 parts of N,N-diethyl-1,3-propylenediamine to the solution obtained in S2, and ultrasonically treat for 30 minutes to obtain a lithium-ion battery water-based fire extinguishing agent.

[0050] The preparation method of the starch grafted ammonium phosphate-montmorillonite composite in step S1 comprises the following steps:

[0051] Starch pretreatment: 200 g starch and 600 g deionized water were mixed evenly, heated to 60°C for gelatinization, and stirred evenly to obtain a starch solution;

[0052] Surface treatment of montmorillonite: 100 g of montmorillonite with a particle size of 50 nm was dispersed in 500 mL of a dispersant solution, stirred at 40° C. for 2 hours, and surface treated to obtain a montmorillonite dispersion; wherein the dispersant included 300 mL of a 3 wt % sodium dodecyl sulfate solution and 200 mL of a 2 wt % ethyl acetate solution.

[0053] Starch grafted ammonium phosphate: 100 mL of the montmorillonite dispersion was added dropwise to 133 mL of the starch solution under continuous stirring. After stirring evenly, 23.75 g of ammonium phosphate and 0.665 g of ammonium persulfate were added. The mixture was reacted at 50° C. for 4 hours under continuous stirring to obtain a primary product.

[0054] Post-treatment: The primary product is filtered, washed and dried to obtain a starch-grafted ammonium phosphate-montmorillonite composite.

[0055] Example 2

[0056] The preparation process of the lithium ion battery water-based fire extinguishing agent provided in this embodiment comprises the following steps:

[0057] S1, mixing 35 parts of starch grafted ammonium phosphate-montmorillonite composite with 80 parts of water, and adding 1.8 parts of sodium carboxymethyl cellulose to obtain a composite suspension;

[0058] S2, adding 25 parts of xylitol, 10 parts of saponin, 5 parts of potassium perfluorobutyl sulfonate, 15 parts of diethylene glycol monobutyl ether, 6 parts of nano-silicon dioxide, and 0.65 parts of sodium carboxymethyl cellulose to the composite suspension in sequence, and stirring at room temperature for 1 hour;

[0059] The total amount of sodium carboxymethyl cellulose added to S1 and S2 is 7% of the starch-grafted ammonium phosphate-montmorillonite composite.

[0060] S3. Add 5 parts of N,N-diethyl-1,3-propylenediamine to the solution obtained in S2, ultrasonically treat for 30 minutes, add 3.67 parts of guar gum, stir for 30 minutes, and obtain a lithium ion battery water-based fire extinguishing agent.

[0061] The preparation method of the starch grafted ammonium phosphate-montmorillonite composite in step S1 comprises the following steps:

[0062] Starch pretreatment: Mix 200g starch and 1000g deionized water evenly, heat to 80°C for gelatinization, and stir evenly to obtain a starch solution;

[0063] Surface treatment of montmorillonite: 100 g of montmorillonite with a particle size of 40 nm was dispersed in 800 mL of a dispersant solution, stirred at 60° C. for 1 hour, and surface treated to obtain a montmorillonite dispersion; wherein the dispersant included 480 mL of a 3 wt % sodium dodecyl sulfate solution and 320 mL of a 2 wt % ethyl acetate solution.

[0064] Starch grafted ammonium phosphate: 100 mL of the montmorillonite dispersion was added dropwise to 198 mL of the starch solution under continuous stirring. After stirring evenly, 23.6 g of ammonium phosphate and 0.66 g of ammonium persulfate were added. The mixture was reacted at 70° C. for 2 hours under continuous stirring to obtain a primary product.

[0065] Post-treatment: The primary product is filtered, washed and dried to obtain a starch-grafted ammonium phosphate-montmorillonite composite.

[0066] Example 3

[0067] The preparation process of the lithium ion battery water-based fire extinguishing agent provided in this embodiment comprises the following steps:

[0068] S1, mixing 30 parts of starch grafted ammonium phosphate-montmorillonite composite with 80 parts of water, and adding 1.3 parts of sodium carboxymethyl cellulose to obtain a composite suspension;

[0069] S2, add 20 parts of sorbitol, 7 parts of saponin, 4 parts of potassium perfluorobutyl sulfonate, 12 parts of diethylene glycol monobutyl ether, 5 parts of nano-silicon dioxide, and 0.5 parts of sodium carboxymethyl cellulose to the composite suspension in sequence, and keep stirring at room temperature for 1 hour;

[0070] The total amount of sodium carboxymethyl cellulose added to S1 and S2 is 6% of the starch-grafted ammonium phosphate-montmorillonite composite.

[0071] S3. Add 4 parts of N,N-diethyl-1,3-propylenediamine to the solution obtained in S2, ultrasonically treat for 30 minutes, then add 4.9 parts of guar gum, stir for 30 minutes, and obtain a lithium ion battery water-based fire extinguishing agent.

[0072] The preparation method of the starch grafted ammonium phosphate-montmorillonite composite in step S1 comprises the following steps:

[0073] Starch pretreatment: Mix 200 g starch and 800 g deionized water, heat to 70°C for gelatinization, and stir evenly to obtain a starch solution;

[0074] Surface treatment of montmorillonite: 100 g of montmorillonite with a particle size of 30 nm was dispersed in 600 mL of a dispersant solution, stirred at 50° C. for 1.5 hours, and surface treated to obtain a montmorillonite dispersion; wherein the dispersant included 360 mL of a 3 wt % sodium dodecyl sulfate solution and 240 mL of a 2 wt % ethyl acetate solution.

[0075] Starch grafted ammonium phosphate: 100 mL of the montmorillonite dispersion was added dropwise to 210 mL of the starch solution under continuous stirring. After stirring evenly, 30 g of ammonium phosphate and 0.84 g of ammonium persulfate were added. The mixture was reacted at 60° C. for 3 hours under continuous stirring to obtain a primary product.

[0076] Post-treatment: The primary product is filtered, washed and dried to obtain a starch-grafted ammonium phosphate-montmorillonite composite.

[0077] Example 4

[0078] The preparation process of the lithium ion battery water-based fire extinguishing agent provided in this embodiment comprises the following steps:

[0079] S1, mixing 30 parts of starch grafted ammonium phosphate-montmorillonite composite with 80 parts of water, and adding 1.4 parts of sodium carboxymethyl cellulose to obtain a composite suspension;

[0080] S2, add 18 parts of sorbitol, 8 parts of saponin, 4 parts of potassium perfluorobutyl sulfonate, 10 parts of diethylene glycol monobutyl ether, 4 parts of nano-silicon dioxide, and 0.4 parts of sodium carboxymethyl cellulose to the composite suspension in sequence, and keep stirring at room temperature for 1 hour;

[0081] The total amount of sodium carboxymethyl cellulose added to S1 and S2 is 6% of the starch-grafted ammonium phosphate-montmorillonite composite.

[0082] S3. Add 4 parts of N,N-diethyl-1,3-propylenediamine to the solution obtained in S2, ultrasonically treat for 30 minutes, then add 6.19 parts of guar gum, stir for 30 minutes, and obtain a lithium ion battery water-based fire extinguishing agent.

[0083] The preparation method of the starch grafted ammonium phosphate-montmorillonite composite in step S1 comprises the following steps:

[0084] Starch pretreatment: Mix 200 g starch and 800 g deionized water, heat to 75°C for gelatinization, and stir to obtain a starch solution;

[0085] Surface treatment of montmorillonite: 100 g of montmorillonite with a particle size of 20 nm was dispersed in 500 mL of a dispersant solution, stirred at 45° C. for 1.5 hours, and surface treated to obtain a montmorillonite dispersion; wherein the dispersant included 300 mL of a 3 wt % sodium dodecyl sulfate solution and 200 mL of a 2 wt % ethyl acetate solution.

[0086] Starch grafted ammonium phosphate: 100 mL of the montmorillonite dispersion was added dropwise to 240 mL of the starch solution under continuous stirring. After stirring evenly, 34.3 g of ammonium phosphate and 0.96 g of ammonium persulfate were added. The mixture was reacted at 55° C. for 3 hours under continuous stirring to obtain a primary product.

[0087] Post-treatment: The primary product is filtered, washed and dried to obtain a starch-grafted ammonium phosphate-montmorillonite composite.

[0088] Comparative Example 1

[0089] Except that starch grafted ammonium phosphate-montmorillonite composite and sodium carboxymethyl cellulose are not added in step S1, the rest is the same as that in Example 3.

[0090] Comparative Example 2

[0091] Except that saponin and nano-silica are not added in step S2, the rest is the same as that in Example 3.

[0092] Comparative Example 3

[0093] Except that starch grafted ammonium phosphate-montmorillonite composite and sodium carboxymethyl cellulose are not added in step S1, and nano silicon dioxide is not added in step S2, the rest is consistent with Example 3.

[0094] 18650 lithium-ion batteries were used as test objects, and the water-based fire extinguishing agents prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were used for testing.

[0095] Specifically, the water-based fire extinguishing agent prepared in Examples 1 to 4 and Comparative Examples 1 to 3 was loaded into a spray gun, the nozzle pressure was set to 0.5 MPa, the flow rate was controlled at 5 L / min, and the nozzle outlet diameter was 3 mm.

[0096] Prepare six groups of 18650 lithium-ion batteries, three batteries in each group, and place them in safe fireproof containers. Connect the positive and negative electrodes of each group of lithium-ion batteries to the positive and negative electrodes of lithium-ion batteries respectively, and gradually increase the current and voltage to overcharge the batteries. When the batteries begin to heat up, smoke, or even flame, a small lithium-ion battery fire has been successfully caused.

[0097] Fire extinguishing performance test:

[0098] After the battery has an open flame, keep burning for 10 seconds, use a spray gun filled with a water-based fire extinguishing agent, stand 1.5 meters away from the fire source and continue to spray the fire extinguishing agent until the flame is completely extinguished. The fire extinguishing time is timed, and the results are shown in Table 1.

[0099] Table 1

[0100] Group Fire extinguishing time(s) Example 1 7 Example 2 5 Example 3 5 Example 4 8 Comparative Example 1 14 Comparative Example 2 10 Comparative Example 3 19

[0101] Cooling performance test:

[0102] After the battery has an open flame, keep burning for 10 seconds, use a spray gun equipped with a water-based fire extinguishing agent, stand 1.5m away from the fire source and continue to spray the fire extinguishing agent until the flame is completely extinguished. Use an infrared thermometer to measure the initial temperature T0 of the battery surface and the temperature T1 when the battery has an open flame, and measure the battery surface temperature T at different time points after spraying the water-based fire extinguishing agent. 10 、T 20 、T 30 、T 45 、T 60 (10s, 20s, 30s, 45s, and 60s after the water-based fire extinguishing agent was sprayed, respectively). The results are shown in Table 2.

[0103] Table 2

[0104]

[0105]

[0106] Anti-reignition performance test:

[0107] After the battery has an open flame, keep burning for 10 seconds, use a spray gun with a water-based fire extinguishing agent, stand 1.5 meters away from the fire source and continue to spray the fire extinguishing agent until the flame is completely extinguished. Observe whether the battery burns again within a period of time (0.5 hours, 1 hour) after the fire is extinguished.

[0108] No re-ignition phenomenon occurred in Examples 1 to 4 and Comparative Examples 1 to 3.

[0109] It can be known that the lithium-ion battery water-based fire extinguishing agent provided in the embodiment of the present application can complete the fire extinguishing of the lithium-ion battery in 5 seconds, and cool down quickly in the 10th second after the fire extinguishing agent is sprayed, that is, the cooling effect of water is dominant, and the evaporation of water takes away the heat, thereby quickly reducing the battery temperature. At the same time, the starch grafted ammonium phosphate-montmorillonite complex decomposes at high temperature, releasing non-combustible gas, diluting the oxygen concentration around the battery, and playing a flame retardant role; at the same time, the phosphoric acid and other substances produced by the decomposition of the starch grafted ammonium phosphate-montmorillonite complex form a heat-insulating and oxygen-isolating protective layer on the battery surface to prevent the continuation of combustion.

[0110] Subsequently, with the continuous spraying of water-based fire extinguishing agent, the evaporation and heat absorption process of water continues, continuously reducing the battery temperature. As the battery temperature decreases, the layered structure of montmorillonite can further block the transfer of oxygen and heat, enhancing the flame retardant effect. Nano-silicon dioxide also helps to improve the stability and heat resistance of the fire extinguishing agent, reduce the transfer of heat to the interior of the battery, and further slow down the chemical reaction rate inside the battery. The protective layer formed by the components in the fire extinguishing agent on the battery surface is more stable. Nano-silicon dioxide and other components form a protective film on the battery surface to prevent the combustible materials inside the battery from contacting with oxygen and avoiding re-ignition.

[0111] The present application also provides a lithium-ion battery water-based fire extinguishing agent, which is prepared by any one of the preparation processes in the above-mentioned embodiments 1 to 4.

[0112] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A lithium-ion battery water-based fire extinguishing agent, characterized in that: In parts by mass, it includes: 70-80 parts of water, 25-35 parts of starch grafted ammonium phosphate-montmorillonite composite, 15-25 parts of polyol, 5-10 parts of saponin, 3-5 parts of potassium perfluorobutyl sulfonate, 10-15 parts of diethylene glycol monobutyl ether, 3-5 parts of N,N-diethyl-1,3-propylenediamine, 4-6 parts of nano silicon dioxide, and sodium carboxymethyl cellulose, wherein the sodium carboxymethyl cellulose accounts for 5-7% of the mass of the starch grafted ammonium phosphate-montmorillonite composite; The starch grafted ammonium phosphate-montmorillonite composite comprises starch, montmorillonite, ammonium phosphate, ammonium persulfate, ethyl acetate and sodium dodecyl sulfate; The preparation method of the starch grafted ammonium phosphate-montmorillonite composite comprises the following steps: Starch pretreatment: Mix starch and deionized water in a mass ratio of 1:3-1:5, heat to 60-80°C for gelatinization, and stir evenly to obtain a starch solution; Surface treatment of montmorillonite: dispersing montmorillonite of 20-50 nm in a dispersant solution at a mass volume ratio of 1:5-1:8, stirring at 40-60° C. for 1-2 hours, and performing surface treatment to obtain a montmorillonite dispersion, wherein the dispersant solution comprises 3 wt % of sodium dodecyl sulfate solution and 2 wt % of ethyl acetate solution, and the volume ratio of the sodium dodecyl sulfate solution to the ethyl acetate solution is 3:2; Starch grafted ammonium phosphate: the montmorillonite dispersion is added dropwise to the starch solution under continuous stirring, so that the mass ratio of montmorillonite to starch is 1:2-1:

3. After stirring evenly, ammonium phosphate and ammonium persulfate are added, and under continuous stirring, the mixture is reacted at 50-70° C. for 2-4 hours to obtain a primary product, wherein the mass ratio of ammonium phosphate to starch is 1:1.4, and the ammonium persulfate is 2% of the mass of the starch. Post-treatment: The primary product is filtered, washed and dried to obtain a starch-grafted ammonium phosphate-montmorillonite composite.

2. The lithium-ion battery water-based fire extinguishing agent according to claim 1, characterized in that: The polyol includes one of xylitol and sorbitol.

3. The lithium-ion battery water-based fire extinguishing agent according to claim 1, characterized in that: It also includes guar gum, and the guar gum accounts for 2-4% of the total mass of the fire extinguishing agent.

4. A process for preparing a lithium-ion battery water-based fire extinguishing agent, which is used to prepare the lithium-ion battery water-based fire extinguishing agent as claimed in any one of claims 1 to 3, characterized in that: It includes the following steps: S1, mixing 25-35 parts of starch grafted ammonium phosphate-montmorillonite composite with 70-80 parts of water, and adding sodium carboxymethyl cellulose to obtain a composite suspension; S2, adding 15-25 parts of polyol, 5-10 parts of saponin, 3-5 parts of potassium perfluorobutyl sulfonate, 10-15 parts of diethylene glycol monobutyl ether, 4-6 parts of nano-silicon dioxide and sodium carboxymethyl cellulose to the composite suspension in sequence, and stirring at 25° C. for 1 hour, wherein the total amount of sodium carboxymethyl cellulose added to S1 and S2 is 5-7% of the starch grafted ammonium phosphate-montmorillonite composite; S3. Add 3 to 5 parts of N,N-diethyl-1,3-propylenediamine to the solution obtained in S2, and ultrasonically treat for 30 minutes to obtain a lithium-ion battery water-based fire extinguishing agent.

5. The preparation process of the lithium ion battery water-based fire extinguishing agent according to claim 4, characterized in that: In the S3, after adding N,N-diethyl-1,3-propylenediamine and ultrasonic treatment, it also includes: Add 2-4% guar gum of the total mass of the solution to the solution after ultrasonic treatment, stir for 30 minutes, and obtain a lithium ion battery water-based fire extinguishing agent.

Citation Information

Patent Citations

  • Fire retardant coating and preparation method thereof

    CN103131288A

  • Preparation method for dendritic organic / inorganic hybrid fire retardant

    CN103435846A

Cited By

  • Water-based fire extinguishing agent based on inorganic silicon dioxide aerogel loaded metal oxide nanoparticles, preparation method and application

    CN121534361A